Hubungan Psikolinguistik dalam Pemerolehan dan Pembelajaran Bahasa - Ayu Sekarsari; Chairunnisa S; Dika Sabilla; Darma Subianto; Sahkholid Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article aims to examine the relationship between psycholinguistics in language acquisition and learning through a conceptual qualitative approach based on literature review. The discussion explores how cognitive, neurological, and affective aspects within psycholinguistics contribute to the processes of first and second language acquisition, and how these insights inform language teaching strategies in educational settings. Rather than focusing on empirical data or specific field sites, this study synthesizes and systematically analyzes findings and theoretical developments from recent scholarly literature in psycholinguistics and language education. The method employed is a theoretical content analysis of reputable academic sources. The findings highlight a strong interconnection between brain mechanisms, mental processes, and social input in the language acquisition process. Moreover, integrating theories of language acquisition and language learning strengthens pedagogical approaches that are responsive to learners’ individual needs. This article contributes conceptually to the interdisciplinary understanding among linguistics, psychology, and education, and offers a foundation for future empirical studies that may apply these theoretical insights in practical contexts.